Use the Force: scaling of jaw muscle forces in the great sculpin, Myoxocephalus polyacanthocephalus - Conrades, Anna D.; Gidmark, Nicholas J. (Friday Harbor Laboratories, 2014)
Suction feeding is the most common vertebrate feeding mode. Fishes suction feed by rapidly expanding the buccal cavity, creating a subambient pressure inside the mouth that causes water (and, ideally, a prey item) to rush in. The predator’s ability to close the mouth around evasive prey determines feeding success. As a fish grows, the volume it engulfs should scale with length to the third power (volume ∝ length3). This becomes a burden on larger fishes, as muscle force (which drives mouth closing) should scale with length squared (force ∝ muscle cross-sectional area ∝ length2). Since suction volume increases faster with size than muscle force, a force deficit results as fish grow larger. Previous studies show that great sculpin counter the force deficit with increased jaw leverage and more force production at longer fish lengths. In this study, we examined muscle force and muscle strain variation across sizes in the suction- feeding great sculpin, Myoxocephalus polyacanthocephalus. Because muscles are subject to the limitations of the length-tension relationship, we saw maximum force (P0) production at intermediate muscle lengths (L0) and declining forces at longer/shorter muscle lengths. Our results show that great sculpin maintain a constant amount of muscle strain to achieve at least 50% of their maximum force (P0) throughout ontogeny. As the great sculpin grows, it uses a wider range of this available muscle strain in feeding, stretching its muscles away from L0 and losing force in the process. Thus in addition to an increasing muscle force deficit, larger great sculpin experience declining jaw-closing forces due to the length-tension properties of jaw- closing muscles.
Keywords: Myoxocephalus polyacanthocephalus, scaling, rictalis, force transducer, suction feeding, sonometric transducer